Social Robots for Service Environments in Academia - Zapata, Mireya (2024)
The increase of social robots in services has generated academic interest in their design and development to enhance human-robot interaction across various contexts, from home assistance to educational and medical environments. Design criteria increasingly explore the software development aspect, but interdisciplinary focus on sustainability also pursues hardware improvement for human-robot interaction in contexts ranging from home assistance to medical environments. With this background, the research question arises: What key features should be considered for the development of a social robot in academia? A systematic metadata review according to PRISMA of 698 studies from the SCOPUS database was conducted, selecting 10 relevant ones to explore functions and applications that allow characterizing hardware and software in the design of social robots for development in academia. Preliminary results indicate a focus on creating smarter, safer, and more adaptable robots, utilizing advances in hardware and software such as flexible electronics and artificial intelligence. It is concluded that the balance between hardware and software proposes the prototyping of a robotic platform with LiDAR/ROS technology, flexible electronics, and ultralightweight material structure, for sustainable, low-power consumption, and low-cost developments. Collaboration among researchers, educators, and developers is crucial to create educational social robots that are both useful and accepted.